Effectiveness of Nurse Led-home Based Diabetic Management Program on Glycemic Control and Quality of life of People Living with Diabetes: A Systematic Review - J. Deaver, Uma; Jyoti, Sarin (International Journal of Nursing Research, 2023)
Background: Diabetes mellitus (DM) is common medical condition which is prevalent among all the age groups due to which the quality of life (QOL) of the individuals gets affected. With this background, systematic literature search and metaanalysis were carried out. Objective: The objective of the study was to assess the effectiveness of nurse led-home based diabetic management program (N-HBDMP) on glycemic control and QOL among people living with diabetes (PLD), with particular focus on its efficacy as an adjunctive treatment. Materials and Methods: Reviewers searched nine databases for systematic reviews published in English language peer-reviewed journals between 2005 and 2018. Systematically, the search of significant articles was carried out in various search engines with the following key words: “PLD,” “Glycemic Control,” “QOL,” and “N-HBDMP.” Results were narrated and synthesized. Results: Thirty-five papers were retrieved from the search. Among them, 25 were evaluated to be of higher quality. Studies recruiting samples of diabetic people with type 2 DM, with various risk factors or those who were dependent on care were insufficient according to high incidence rate of T2DM. Conclusion: The incidence of T2DM, its related symptoms, and its complications can be reduced by the N-HBDMP which deals with controlling the glycemic level and improving the QOL of PLD.